PENERAPAN PROGRAM COMMUNICATION FOR BEHAVIOURAL IMPACT (COMBI ) DALAM MENCIPTAKAN LINGKUNGAN SEKOLAH BEBAS JENTIK - Asriwati; Harjati; Irawati; Eko Nugroho (Bajang Institute, 2021)
Disease prevention and health promotion are essential efforts when the high incidence of infectious diseases is also accompanied by the increasing problem of non-communicable diseases. Many studies have found that government top-down health promotion and disease prevention efforts are less effective when compared to community-based programs. Therefore, to support the concept of a Healthy School that has just been launched by the government, it is necessary to mobilize the community to familiarize a healthy life in accordance with the objectives of a healthy, free larvae school program. Initiation should start from the smallest community groups such as schools. School is a gathering place for school-age children and its half-life is more schooled than at home, school children who are the nation's next generation to produce a healthy and strong generation